Modelling the Growth of Enterobacter sp. on Polyethylene (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Although standard, the use of linearization techniques using natural logarithm transformation is erroneous and can only give an estimated value for the measured parameter; the specific growth rate. For the first time, in this paper, we present different kinetic models such as Von Bertalanffy, Baranyi-Roberts, modified Schnute, modified Richards, modified Gompertz, modified Logistics and most recent Huang were employed to obtain values for the above constants or parameters from Enterobacter sp. growth on polyethylene. Huang model was found to be the best model with the highest adjusted R2 value and lowest RMSE value. The Accuracy and Bias Factors values were close to unity (1.0). The Huang parameters such as Ymax (bacterial growth upper asymptote), Î» (lag time), Âµmax (maximum specific bacterial growth rate) and A or Y0 (bacterial growth lower asymptote) were found to be 1.367 (95% confidence interval of 1.322 - 1.412), 2.683 (95% confidence interval of 2.030 - 3.337), 0.322 (95% confidence interval of 0.252 - 0.392) and 0.324 (95% confidence interval of 0.278 - 0.370).
Keywords: Polyethylene, Entrobacter sp, Mathematical modelling, growth, Huang